Knowledge and practices regarding management of minor ailments of pregnancy among antenatal mothers: a descriptive study from Rajasthan - Sharma, Ankita; Rani, Raj; Nebhinani, Mamta; Singh, Pratibha (International Journal Of Community Medicine And Public Health, 2020)
Background: Pregnancy is considered as one of the most beautiful events in every female life which brings a lot of physiological and hormonal changes to prepare women for motherhood. Even though these changes are not dangerous, still they are bothersome. Women use number of homemade remedies to alleviate these discomforts. Objective: The objective of this study was to assess knowledge and practices regarding management of minor ailments of pregnancy among antenatal mothers. Methods: This study was conducted at obstetrics OPD of All India Institute of Medical Sciences, Jodhpur, Rajasthan. 368, 3rd trimester pregnant mothers were recruited by convenient sampling technique. Self- structured knowledge questionnaire, checklist for practice were used for data collection using face to face interview method. Results: Most common health problems as reported by pregnant women were increased urine frequency and fatigue. Nearly 61% of mothers had fair knowledge levels. Majority of the antenatal mothers used one or another home remedy to alleviate their symptoms. 86.6% ate small and frequent meals followed by 74.3% avoided strong odors to prevent nausea and vomiting. Conclusion: Increased urine frequency is the most evident minor ailment faced during pregnancy. Overall antenatal mothers had fair knowledge regarding management of minor ailments and varied practices have been performed by antenatal mothers to relieve their problems. There is a need to conduct aggressive and comprehensive health promotion and awareness sessions for the expectant mothers so as to manage these ailments and prevent further complications.